State of knowledge on teacher training with a focus on higher education and public policies: teacher training in dispute (Olhar de Professor, 2022)
This article proposes the discussion about teacher training with a focus on higher education and public policies based on elements of disputes. The aim of the study is to understand what the area of education investigates about teacher training, focusing on higher education policies, in order to provide theoretical subsidies that enable a consistent debate about the implications of educational reforms for teacher training in Brazil. The methodology used was the State of Knowledge and content analysis for data collection, categorization, and analysis. The texts were extracted from the SciELO database. We conclude that it is possible to verify that teacher training is marked by the supremacy of the interests of capital characterized by the theory of competencies and by the BNCC's own skills that permeate Resolution CNE/CP nº 2/2019 and ensure in the field of educational policies the interests of neoliberal privatized groups.
Keywords: Teacher training.; Educational policies.; Public policies.